Redesain Kemasan Dadiah Minangkabau: Integrasi Model AISAS dalam Meningkatkan Portabilitas dan Daya Tarik Visual bagi Wisatawan - Maulid, Amy; Sari, Dian Fitriarni; Heruningrum, Heruningrum; Fuad, Saftrian Mukhlizul (Jurnal Ilmiah Pariwisata, 2026)
Traditional cuisine such as dadih, a fermented buffalo milk product from the Minangkabau culture, represents both cultural identity and a tourism attraction in West Sumatra. However, the product is still marketed using traditional bamboo packaging that is less practical and lacks a strong visual identity in the modern market. This study aims to analyze the limitations of traditional dadih packaging and to formulate a redesigned packaging concept that is more practical, informative, and visually appealing through the integration of the AISAS model, which includes attention, interest, search, action, and share. The research adopts a qualitative approach using an exploratory case study design combined with an ethnographic perspective. Data were collected through field observations and in-depth interviews with five informants consisting of dadih producers, buffalo farmers, culinary business actors, and consumers. Data analysis was conducted using thematic analysis to identify consumer perceptions regarding product identity, visual attractiveness, and packaging functionality. The findings reveal that traditional packaging limits product visibility and influences consumers’ purchase interest. Redesigned packaging that incorporates cultural identity and product information can enhance consumer attention and interest. This study concludes that packaging innovation and digital communication strategies can strengthen the competitiveness of dadih as a traditional culinary product. Keywords: Dadih, traditional cuisine, packaging redesign, AISAS model, gastronomic tourism, digital marketing